Phantom Pain: On the Reception of Renaissance Art in the Modern Epoch - Rykov, Anatolii V. (Actual Problems of Theory and History of Art, 2016)
The paper explores proto-political connotations of Pavel Muratov’s critical works — one of the most vivid examples of utopian thinking in Russian art historiography. The author makes an attempt to reconstruct a political context of Pavel Muratov’s Images of Italy, probably the most famous text on the reception of Renaissance art in the history of Russia. Special attention has been paid to the philosophical foundations of Muratov’s views such as vitalism, “philosophy of life”, theories of regeneration, and the ideas of a “conservative revolution” in Germany. Muratov’s aestheticism has a relation to Walter Benjamin’s conception of aesthetic politics and contemporary theories of totalitarianism. The paper traces the transformation of Muratov’s aestheticism into the classist and nationalistic theory, in different ways connected with fascist ideology. Renaissance art was appropriated by Muratov as a utopian alternative to modernity, democratic art of the “people”, special form of life, spontaneous, joyful, energetic, and alien to bourgeoisie and the upper classes of the society. The author examines the work of populist, anti-intellectualistic discourses in Muratov’s art criticism and draws the conclusion that his oeuvre was especially close to conservative Modernism and the radical political thinking of the conservative revolution. For the first time Muratov’s art criticism is analyzed in the context of his political writings of the 1920s and 1930s. Muratov’s conception of Renaissance art has been interpreted as one of the versions of romantic anti-capitalism.